Comparative Reliability Of Types Of Thermoelectric Generators Based On Three Circuit Variations - Armansyah, Armansyah; Mahrizal Masri; Zulfadli Pelawi; Hermansyah Alam (SEAN Institute, 2023)
In this final project, the characteristics of the thermoelectric generator Type SP1848 27145 SA have been tested using three variations of the circuit, where in the test the three types of circuit use the same cooling and heating sources, the heat source uses the hot fire of a spirit stove and in the cold part uses a tank filled with running water without heatsing. The highest voltage output results were recorded in testing using a series circuit. The voltage recorded in the series circuit test was 19.91 volts, only taking 47.17 seconds.T 44°C but when testing with a load the highest result was recorded in a test using a parallel series circuit, a result of 9.74 watts was recorded atT 44°C and the highest current obtained in the parallel series circuit test recorded a final result of 0.76 amperes.